UMP lost and found mobile application - Muhammad Syafiq, Muhammad Razman Robert (2019)
Since generation, the issue of losing personal belongings is a common thing for all people. Anyone can lose their personal belongings. At Universiti Malaysia Pahang only, almost every week there will be a lot of cases of lost and found personal items such as wallets, matric cards, room keys and so on. Usually, the information regarding the lost and found item was spread by the student himself via the UMP portal in the announcement board and the WhatsApp media. This method is not very efficient because not all students at UMP will receive information about the lost and found items. Hence, UMP Lost and Found Mobile Application is developed to centralized the information regarding all the lost and found items in a mobile application. This app can help students find lost items or track owners for items they have found. Any lost or found items around UMP will be reported and recorded in this mobile app by the students, with all records relating to lost or found items will be easily searched by students to search for their missing items.